PENGGUNAAN WEARABLE TEKNOLOGI UNTUK MEMANTAU AKTIVITAS FISIK MAHASISWA PENDIDIKAN OLAHRAGA - Kubani; Jurya (Jurnal Riset dan Transformasi Pendidikan, 2026)
Wearable technology has become an innovative tool in monitoring physical activity among students in sports education programs. This study aims to analyze the effectiveness of wearable devices in tracking physical activity, heart rate, calorie expenditure, and exercise patterns among sports education students. The research employed a quantitative descriptive method involving 50 sports education students who used wearable devices for four weeks during academic and training activities. Data were collected through activity logs generated by wearable devices and validated through observation sheets and questionnaires. The results indicate that wearable technology provides accurate and real-time monitoring of students’ physical activity, improves awareness of personal fitness levels, and supports data-driven exercise evaluation. Furthermore, wearable devices enhance motivation and self-regulation among students in maintaining regular physical activity. The findings suggest that wearable technology can serve as an effective digital tool in modern sports education for performance monitoring and health management.